The church in the public : a politics of engagement for a cruel and indifferent age - Ahn, Ilsup (Fortress Press, 2022)
The Church in the Public shows how church/state dualism has corrupted the church's social witness and allowed neoliberal and neocolonial ideas to assert control of public and political life. Ahn argues for a public church, one that collaborates and cooperates with other public actors and entities in the promotion of a just social order.